IFN-γ Mediated Signaling Improves Fungal Clearance in Experimental Pulmonary Mucormycosis - dos Santos, Amanda Ribeiro [UNESP]; Fraga-Silva, Thais Fernanda; de Fátima Almeida-Donanzam, Débora [UNESP]; dos Santos, Rodolfo Ferreira [UNESP]; Finato, Angela Carolina [UNESP]; Soares, Cleverson Teixeira; Lara, Vanessa Soares; Almeida, Nara Lígia Martins; Andrade, Maria Izilda; de Arruda, Olavo Speranza [UNESP]; de Arruda, Maria Sueli Parreira [UNESP]; Venturini, James [UNESP] (Springer Nature, 2022)
We established three immunocompetent murine models of pulmonary mucormycosis to determine the involvement of the adaptive immune response in host resistance in pulmonary mucormycosis, a rapidly fatal disease caused mainly by Rhizopus spp. Immunocompetent inbred (C57BL/6, BALB/c) and outbred (Swiss) strains of mice were inoculated with R. oryzae via the intratracheal route. The inoculation resulted in a disseminated infection that spread to the brain, spleen, kidney, and liver. After 7 and 30 days of R. oryzae infection, BALB/c mice showed the lowest fungal load and highest production of IFN-γ and IL-2 by splenocytes. Swiss mice showed a higher fungal load 30 days p.i. and was associated with a weak development of the Th-1 profile. To confirm our findings, R. oryzae-infected IFN-γ−/− mice were evaluated after 60 days, where the mice still showed viable fungi in the lungs. This study showed, for the first time, that pulmonary mucormycosis in three widely used mouse strains resulted in an acute fungal dissemination without immunosuppression whose outcome varies according to the genetic background of the mice. We also identified the partial role of IFN-γ in the efficient elimination of R. oryzae during pulmonary infection.
Keywords: BALB/c mice; C57bl/6 mice; Fungal infection; IFN-γ −/− mice; Rhizopus oryzae; Swiss mice